Association of hemoglobin concentration with bone mineral density in adult females of Dhaka city: Hemoglobin and bone mineral density - Rahman, Nishat; Akhter, Qazi Shamima; Shaha, Manasi; Bushra, Khadijatul; Akter, Mahbuba; Islam, Nawshin; Sarkar, Keya; Rahman, Mostafizur; Jahan, Nusrat (Journal of the Medical College for Women & Hospital, 2024)
Background: Globally osteoporosis is a major public health concern. Various factors have influence on bone mass. Anemia is common in Bangladesh among the women of reproductive age group. This may be a contributing factor to low density of mineral of bone in young adult females. Aim: This research was performed to observe hemoglobin concentration’s association with density of bone mineral in adult females of Dhaka city. Materials and Method: This cross sectional study was performed in the Physiology Department of Dhaka Medical College, Dhaka between 2018 July and 2019 June. One hundred and twenty two female participants in the age range from 18 to 44 years were recruited for the study. The density of mineral of bone measurement was carried out for the eligible subjects after obtaining informed written consent. Data was collected and statistical analysis was done using One-way ANOVA, Bonferroni test and Pearson’s correlation coefficient (r) using SPSS for windows version 25.0. Results: The mean (± SD) hemoglobin concentration of group A, group B and group C were 9.87 ± 0.71, 11.44 ± 0.26, and 12.75 ± 0.75 g/dl respectively. The mean (± SD) bone mass density (BMD) T score of lumbar spine of group A, group B and group C were -0.70 ± 1.01, -0.13 ± 0.85, and -0.03 ± 0.92 respectively. The mean (± SD) BMD T score of femoral neck of group A, group B and group C were -0.75 ± 0.95, -0.19 ± 0.85, and -0.06 ± 0.84 respectively. We found statistically significant positive correlation (r= +0.284 and r= +0.366 respectively) between BMD T score of both lumbar spine and femoral neck with hemoglobin concentration (p=0.001 and p<0.001 respectively). Conclusion: A reduction in hemoglobin concentration may lead to reduced oxygen in blood with stimulation of proteosomal degradation ; osteoclastogenesis and inhibition of osteoblastic bone formation. These changes may cause decrease in bone mineral density. Therefore, early detection of anemia may help prevent reduction in density of bone mineral and maintain bone health. J Med Coll Women Hosp.2024;20(1):23-31